Antimicrobial Resistance in Veterinary Medicine and Public Health - Roncada, Paola; Tilocca, Bruno (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Antimicrobial resistance is the intrinsic capability of microorganisms to survive unfavorable conditions; such traits are mainly transferrable through movable genetic elements, enabling the rapid and homogeneous diffusion of resistance genes over diverse ecosystems and sectors including human medicine, veterinary medicine, and the environment. In this view, the One Health approach allows for a comprehensive depiction of the mechanisms responsible for the onset and spread of antimicrobial resistance traits, as well as enabling a clear definition of the dynamics that occurs among microbial members harboring diverse ecological niches that favor the orthogonal diffusion of antibiotic resistance between apparently separate milieus.